Study of secondary hemo-phagocytic lympho-histiocytosis in children at a tertiary centre - Kantharajanna, Usha B.; A., Pragalatha Kumar; S., Sanjay K.; Chebbi, Pooja Gujjal; Tenneli, Anil Kumar (International Journal of Contemporary Pediatrics, 2021)
Background: Hemophagocytic lympho-histiocytosis (HLH) is fatal condition characterised by aggressive immune activation, dysregulation and up regulation of inflammatory cytokines leading to uncontrolled activation of T-cells, defective granule mediated cytotoxicity. HLH is classified into primary and secondary HLH. Methods: This is retrospective study of case-records of children who fulfilled criteria of HLH-2004 guidelines from November 2016 to November 2020. Results: Total number of patients with HLH was 33, excluding 4 cases of primary HLH, 29 cases met the inclusion criteria. 19 (65.5%) were children less than 5 years of age at the time of diagnosis. Six (20.7%) children were between 6 to 10 years and the rest 4 (13.8%) ten years. Average age at presentation was 4.93 years. Male to female ratio was 0.8 to 1. Fever was the chief complaint present in 29 (100%) of cases. Laboratory parameters showed anaemia, thrombocytopenia, hyper-ferritinemia and hypertriglyceridemia in all 29 (100%) cases. CRP elevated in 28 (96.6%) cases. Infections found in 29 (100%) of cases, bacteria in 19 (65.5%), viral in 10 (34.5%). Mortality seen in 11 (37.9%) cases. Average time of diagnosis from admission was 5.6 days. 4 children out of 11 had dengue as cause for secondary HLH and 4 had bacterial sepsis one each CMV, scrub typhus and SLE. Following factors affected the outcome by multivariate analysis, coagulopathy, elevated liver enzymes, bone marrow biopsy and immunosuppressive therapy. Conclusions: HLH should be considered in differential diagnosis of children with sepsis. High index of suspicion for HLH with early initiation of treatment should be considered for better outcome.